(untitled) (Research, Society and Development, 2021)
The study aimed to identify the correlation between chronic diseases and medication use in elderly people diagnosed with depression. The research was cross-sectional, descriptive and analytical in medical records of patients treated at the Elderly Health Outpatient Clinic of the Medical Specialties Center of the University Center of the State of Pará (CEMEC), after institutional acceptance and approval by the Research Ethics Committee. Data were collected from the medical records of 155 patients aged 60 years or over, of both genders, through a questionnaire, with the backing variables: medical record number, age, depression diagnosis, use and number of medications and associated comorbidities. It was detected that 60.53% of the elderly used 4 to 6 medications, 55.26% of them had 4 to 6 comorbidities, the most frequent being SAH, with 81.58% of the elderly depressed. Parkinson’s disease (5.26%) and cerebrovascular accident (5.26%) appear as the same frequent comorbidities, followed by Major Neurocognitive Disorder of the Alzheimer type (7.89%). This research manifested that among the elderly who had depression and used polypharmacy, the most usual was hipertension, which can be concluded that depressive illness is a possible risk factor for the development of cardiovascular diseases. Therefore, it can be said that, for a better quality of life of the aged person with depression, it is essential to support the family, activities that promote well-being, leisure tasks and physical exercise, with the aim of releasing more serotonergic neurotransmitters.